2010
DOI: 10.1007/s11757-010-0086-z
|View full text |Cite
|
Sign up to set email alerts
|

Die Validität dynamisch-veränderbarer Risikofaktoren bei der Vorhersage einschlägiger Rückfälle pädosexueller Straftäter

Abstract: Zusammenfassung gegenstand der vorliegenden arbeit ist die Überprüfung der Prognosegüte dynamischer risikoparameter zur Vorhersage einschlägiger rückfälle bei einer Stichprobe pädosexueller täter (n = 135), die zwischen 2002 und 2005 aus dem österreichischen Strafvollzug entlassen wurden. Zur erfassung der statischen Variablen wurde der Static-99, zur erfassung der (stabil-)dynamischen risikoparameter der Stable-2000 sowie dessen nachfolgeversion, der Stable-2007, verwendet. neben der interraterreliabilität, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 34 publications
0
8
0
5
Order By: Relevance
“…As of April 25, 2018, our search yielded 21 studies consisting of 12 nonoverlapping samples (see the appendix). The vast majority of studies were produced in English ( k = 18), and two studies were in German (Eher et al, 2013; Rettenberger, Matthes, Schilling, & Eher, 2011). Six studies reported on nonoverlapping samples, one study (Looman & Goldstein, 2015) contained two different samples that were divided into a routine and a high-risk/need sample, and a further 13 studies represented four overlapping samples, resulting in 12 unique samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As of April 25, 2018, our search yielded 21 studies consisting of 12 nonoverlapping samples (see the appendix). The vast majority of studies were produced in English ( k = 18), and two studies were in German (Eher et al, 2013; Rettenberger, Matthes, Schilling, & Eher, 2011). Six studies reported on nonoverlapping samples, one study (Looman & Goldstein, 2015) contained two different samples that were divided into a routine and a high-risk/need sample, and a further 13 studies represented four overlapping samples, resulting in 12 unique samples.…”
Section: Methodsmentioning
confidence: 99%
“…To be included in the current meta-analysis, the study had to include adult males convicted of a sexual offense, ratings on STABLE-2007 (or STABLE-2000 and sufficient information to compute STABLE-2007 scores), a follow-up period in which recidivism was recorded, and sufficient information to calculate an effect size. Authors from nine of the 12 samples provided their original datasets for the current meta-analysis; additional effect sizes and information were collected from the authors of the remaining samples (Eher et al, 2012; Eher et al, 2013; Rettenberger et al, 2011; Sowden & Olver, 2017). A coding manual containing a standard list of variables and explicit coding rules is included in the Supplemental Material (and available upon request).…”
Section: Methodsmentioning
confidence: 99%
“…The interrater reliability of the German versions of the Stable-2000 and the Stable-2007 was examined by using the total scores of two independent clinicians who have worked at the FECVSO for n = 10 cases derived from the total sample of the present study (Rettenberger, Matthes, Schilling, & Eher, 2011). Both independent raters had access to the files and both had conducted an independent clinical interview with the offender.…”
Section: Methodsmentioning
confidence: 99%
“…4 Zwar ist dieser auf den ersten Blick paradoxe Zusammenhang nicht zwangsläufig als problematisch anzusehen, er scheint jedoch für die Entstehung von Schwierigkeiten in der sexuellen Selbstregulierung relevant zu sein, wie sie bei Personen, die zwanghaftsüchtiges bzw. hypersexuelles Verhalten, sexuelles Risikoverhalten oder sexuell delinquentes Verhalten zeigen, vorliegen können (Briken et al 2008;Briken und Basdekis-Josza 2010;Rettenberger et al 2011Rettenberger et al , 2013. Das Duale Kontrollmodell könnte eine mögliche Erklärung dafür liefern, warum bei bestimmten Personen das genannte, zunächst paradox erscheinende Erregungsmuster im Falle negativer Gemütszustände auftritt: Personen mit höherer SES und gleichzeitig niedrigerer SIS könnten eher dazu neigen, sexuelle Aktivität und Verlangen im Sinne eines Coping-Mechanismus zur Stimmungsstabilisierung zu nutzen (Bancroft et al 2009).…”
Section: Die Relevanz Des Dualen Kontrollmodells Für Die Sexualwissenunclassified